2004
DOI: 10.1590/s0103-50532004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead in bone by electrothermal atomic absorption spectrometry with Zeeman effect background correction

Abstract: Um método para a determinação de traços de Pb em ossos por espectrometria de absorção atômica é descrito. Boas precisão e exatidão foram obtidas utilizando-se calibração externa com padrões aquosos e NH 4 H 2 PO 4 como modificador. O limite de detecção alcançado foi de 0,07 ng mL -1 na solução de leitura, correspondendo a 0,022 g g -1 na amostra original. Conseqüentemente, o limite de quantificação encontrado foi de 0,23 ng mL -1 . Uma precisão de 3,5% foi obtida na leitura de 400 ng de Pb na presença da matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The Pd-Mg modifier is the one most commonly used, since it produces the best results. This modifier allows for the application of pyrolysis temperatures ranging from 1200 to 1400 • C, which enables the separation of most interfering elements [13][14][15][16][17]. The stabilizing effect of this modifier also raises the atomization temperature to 2000 • C, which allows a characteristic mass of about 16 pg [13].…”
Section: Atomic Absorption Spectrometry (Aas)mentioning
confidence: 99%
“…The Pd-Mg modifier is the one most commonly used, since it produces the best results. This modifier allows for the application of pyrolysis temperatures ranging from 1200 to 1400 • C, which enables the separation of most interfering elements [13][14][15][16][17]. The stabilizing effect of this modifier also raises the atomization temperature to 2000 • C, which allows a characteristic mass of about 16 pg [13].…”
Section: Atomic Absorption Spectrometry (Aas)mentioning
confidence: 99%
“…Several analytical methods such as X-ray fluorescence (XRF) 13,14,17 , proton-induced X-ray emission (PIXE) 1 , inductively coupled plasma optical emission spectrometry (ICP-OES) 18,19 , two-jet plasma atomic emission spectrometry 20 , inductively coupled plasma mass spectrometry (ICP-MS) alone 2,11,12,21 or combined with laser ablation (LA-ICP-MS) 9,22 , hydride generation (HG-ICP-MS) 23 , atomic fluorescence spectrometry (AFS) 24 or electrothermal atomic absorption spectrometry (ETAAS) 1, 3,6,12,15,16,21,[25][26][27][28][29][30][31][32] previously assessed the validity and limitations for the purpose of quantification of Pb in both human and animal samples. Among these methods, ETAAS 1, 5,10,25,27,[31][32][33][34][35][36] still represents the most commonly used one in routine analytical practice because of its high sensitivity, favourable detection limits and relatively low cost of the instrumentation. However, due to the complex matrix, laborious sample preparation, relatively low analytical concentration and high volatility of some lead species, the analysis of bone or teeth samples is difficult 1, 33,34,37 .…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate these problems attributed to PO molecular absorption, instrumentation with several different background correction systems have been employed 3, 5, 6, 10, 15, 16, 21, 25-27, 30-33, 36, 38, 39 . Among conventional line source atomic absorption spectrometers (LS AAS), Zeeman systems using both transverse 21,31,33,36 and longitudinal 3, 25, 32, arrangement were found 3,5,16,21,25,30,33,34,36,39 to be the most reliable for this purpose. However, it has been shown that under the influence of the magnetic field the rotational lines of molecular spectrum of the gaseous phosphorus monoxide (PO) have split thus making the analysis of samples with high phosphorus content when using Zeeman effect background corrections prone to errors 39,40 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone samples were pulverised, homogenised and dried overnight at 80°C and then left to cool in desiccators. Aliquots of about 1000 mg from each sample were weighed and then digested in a microwave oven (Millestone Ethos D) with a mixture of nitric and perchloric acids at 80°C [41]. After cooling, the solution obtained was transferred to a 50-mL plastic tube and made up to 30 mL with Milli-Q water (18.2 MΩ cm −1 ; ±20°C) and the modifier solution (NH 4 H 2 PO 4 ) according to Pereira et al[41] The Merck certified standard solutions were analysed together with the samples in order to evaluate the analytical quality control.…”
mentioning
confidence: 99%